2012
DOI: 10.1242/jeb.059725
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism in the age of ‘omes’

Abstract: SummaryMuch research in comparative physiology is now performed using ʻomicsʼ tools and many results are interpreted in terms of the effects of changes in gene expression on energy metabolism. However, ʻmetabolismʼ is a complex phenomenon that spans multiple levels of biological organization. In addition rates and directions of flux change dynamically under various physiological circumstances. Within cells, message level cannot be equated with protein level because multiple mechanisms are at play in the ʻregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…The analyses discussed above have attempted to model the systems properties of biological networks using data on the activity of proteins measured in vitro. In vivo, flux through metabolic pathways is most often controlled by variation in the concentrations of substrates, products or allosteric effectors, in what has been termed 'metabolic regulation' (ter Kuile and Westerhoff, 2001;Suarez and Moyes, 2012). Indeed, studies of the thermal dependence of glycolytic flux in yeast suggest that metabolic regulation is the dominant force in determining the response of pathway flux as temperature increases (Postmus et al, 2008).…”
Section: Effects Of Temperature At the Level Of Single Proteinsmentioning
confidence: 99%
“…The analyses discussed above have attempted to model the systems properties of biological networks using data on the activity of proteins measured in vitro. In vivo, flux through metabolic pathways is most often controlled by variation in the concentrations of substrates, products or allosteric effectors, in what has been termed 'metabolic regulation' (ter Kuile and Westerhoff, 2001;Suarez and Moyes, 2012). Indeed, studies of the thermal dependence of glycolytic flux in yeast suggest that metabolic regulation is the dominant force in determining the response of pathway flux as temperature increases (Postmus et al, 2008).…”
Section: Effects Of Temperature At the Level Of Single Proteinsmentioning
confidence: 99%
“…For example, recent large-scale transcriptomic and proteomic studies of the expression of ∼5,000 genes and their corresponding proteins have shown that changes in gene expression are not good measures of protein abundance (40). Even when mRNA predicts protein abundance, physiologically relevant protein activity can vary substantially from patterns of gene expression or protein abundance (41)(42)(43)(44). For comparative studies of marine organisms that lack comprehensive and simultaneous quantification of transcriptomes and proteomes (40), analyses that infer physiological activity from measurements of gene expression should be interpreted with caution.…”
Section: Biochemical Rate Compensation Under Acidificationmentioning
confidence: 99%
“…These observations should be partly due to the well-known kinetic effects of temperature on reaction rates, but could also result from effects on the various physiological factors that control metabolism. Metabolic rate and oxygen consumption are system-level processes that are influenced by all steps in the pathway of oxygen and fuel delivery and oxidation, including the activity of metabolic enzymes and the abundance of mitochondria (Suarez and Moyes, 2012). In this regard, T E has been shown to alter mitochondrial abundance in the muscle of larvae from several fish species (Vieira and Johnston, 1992;Brooks and Johnston, 1993).…”
Section: Research Articlementioning
confidence: 99%